THE EFFECT OF E-SERVICE QUALITY ON E-SATISFACTION THROUGH CORPORATE IMAGE ON ISLAMIC BANK - Albetris Albetris (JURNAL MANAJEMEN DAN BISNIS, 2021)
Competition in banking services such as branchless banking, the use of technological facilities involving third party services, especially to serve the unbanked community, has great potential to expand the distribution of financial services to the public. Models of service marketing (service marketing), relationship marketing (relationship marketing) and digital marketing (digital marketing) need to be studied simultaneously through a banking service marketing management approach to obtain e-Satisfaction. The purpose of this study was to obtain a model of E - Customer Satisfaction at state banks implementing branchless banking as a marketing strategy for banking services, especially branchless banking in Jambi. The research design used an explanatory survey approach. The survey was conducted on customers at a Islamic bank implementing branchless banking in Jambi. The number of respondents was 50 customers who were taken by multistage random sampling. Data analysis was carried out using a structural equation modeling (SEM) approach and the Smart PLS program.This study aims to see that the Customer e-Satisfaction model at the state bank implementing branchless banking needs to consider various factors as a whole in the marketing of services in bank management at the state bank implementing branchless banking in the context of service marketing by enhancing the bank's image (corporate image). ), creating wider relationships through relationship marketing, increasing digital marketing e- satisfaction by using the internet and using interactive technology that involves the application of digital technology, namely; web, e-mail, database, mobile/wireless and others. This can improve e-service quality Corporate image and e satisfaction for customers consistently and continuously by developing an e-loyalty model. In general, banks and especially branchless banking providers are expected to be able to carry out competitive and innovative strategies to respond to the challenges of the digitalization era, where globalization and the rapid evolution of digital technology are industrial revolution 4.0.